2021
DOI: 10.1097/md.0000000000024608
|View full text |Cite
|
Sign up to set email alerts
|

Association of 3 single nucleotide polymorphisms of the eighth chromosome with remodeling of the myocardium and carotid arteries in the Kazakh population

Abstract: Cardiovascular diseases are one of the key health issues in Kazakhstan. According to the WHO, the prevalence of arterial hypertension (AH) was 28% in males and 25% in females in 2015, which puts up vastly to premature mortality from non-communicable diseases. The search for genetic features of target organ lesions processes in AH is relevant. The goal of this study was to search for the genetic markers of myocardial remodeling (MR) and carotid artery remodeling (CAR). A total of 866 hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Although there is a lack of studies investigating on SNPs of 9p21.3 locus in the Kazakh population, other SNPs on other locus were studied. Karabayeva et al showed a significant association of rs2407103, rs11775334, and rs2071518 polymorphisms on the 8th chromosome to myocardial and coronary artery remodeling [16]. Hua et al showed significant relevance of the G allele of rs4977574 and the C allele of rs1333045 to CAD in the Chinese population, including Kazakh ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a lack of studies investigating on SNPs of 9p21.3 locus in the Kazakh population, other SNPs on other locus were studied. Karabayeva et al showed a significant association of rs2407103, rs11775334, and rs2071518 polymorphisms on the 8th chromosome to myocardial and coronary artery remodeling [16]. Hua et al showed significant relevance of the G allele of rs4977574 and the C allele of rs1333045 to CAD in the Chinese population, including Kazakh ethnic groups.…”
Section: Introductionmentioning
confidence: 99%